A study of the alkaloid content of the Senecio speciosus/Macrocephalus complex - Grue, Margaret Ruth (Rhodes University, Faculty of Science, Department of Chemistry, 1992)
The isolation and identification of pyrrolizidine alkaloids from various plant species from 1988 to May 1991 are reviewed and the alkaloids of two indigenous plant species, Senecio speciosus Willd and Senecio macrocephalus DC, were investigated. A brief review of the methods used for isolation and identification of pyrrolizidines is also given. S. speciosus was found to contain two new alkaloids, 7-senecioyl-9-sarracinylheliotridine and 7-isosarracinyl-9- sarracinyl-heliotridine, which were identified using highfield NMR techniques. A number of other alkaloids were tentatively identified using GC-MS. S. macrocephalus contains very little alkaloid, but a number of pyrrolizidine alkaloids were tentatively identified using GC-MS. Standard alkaloids for GC-MS work were obtained both by extraction from a number of plant species and by synthesis of simple monoester alkaloids. In this process the alkaloid neosarracine, previously described by GC-MS, was isolated and NMR data for this compound are reported for the first time. S. speciosus and S. macrocephalus are morphologically very similar and their counterparts in the Grahamstown district exhibit features characteristic of both species. This could be due to hybridization, genetic mutation or simple variation within the species. The alkaloids of four local plant populations were examined in order to collect taxonomic markers whereby it was hoped that the Grahamstown plants could be satisfactorily classified. Three of the plant populations were found to contain 7-senecioyl-9-sarracinylheliotridine and 7-angelyl-9-sarracinyl-heliotridine. One population was found to contain the known alkaloid retrorsine along with the new alkaloid 2-hydroxy-l, 2-dihydrosenkirkine. The alkaloidal fractions of all four populations were compared using GC-MS and NMR techniques. Tentative taxonomic conclusions were drawn.
Keywords: Alkaloids -- Research; Pyrrolizidines -- Research; Botanical chemistry